The Perspective of Islamic Law on a Mismatched Object in Online Sales and Purchases Transactions - Mustikawati, Intan Mukarromah; Handono, Mardi; Zulaika, Emi (Lentera Hukum, 2019)
Online transaction is a cross-personal action done by two or more parties to reach an agreement. The law of sales and purchases in Islam requires the double coincidence of wants as a measure of transaction validity. However, humans will always find the double coincidence of wants as a remote probability. Therefore, the previous Ulamas set an ijab-qabul as a symbolization of the double coincidence of wants. A qabul is an expression of the handed over of one's ownership rights to a particular party, and vice versa, as well as a sign that both of the parties have agreed on the contract (akad). Keywords: Online Transactions, Buying and Selling in Islamic Law, Object Mismatches.